Pengaruh Probabilitas Kebangkrutan Dan Penerapan Good Corporate Governance Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan Perusahaan Pertambangan Di Bursa Efek Indonesia - Dewi, Yesi Kurnia; Retnaningdiah, Dian (Journal Competency of Business, 2023)
This study aims to determine the effect of the Bankruptcy probability and the Implementation of GCG on the Timeliness of Financial Statements Submission of Mining Companies on the Indonesia Stock Exchange. This study employed a quantitative approach using secondary data. The data were collected by means of documentation and literature study. The sample used was 33 mining companies using the purposive sampling method. The data analysis used in this research were Descriptive Statistical Analysis, Classical Assumption Test, Logistic Regression Analysis, Partial Test (T-Test), and Simultaneous Test (F Test). The results obtained indicate that the Audit Committee, Independent Commissioner, and Audit Quality, partially, only the Bankruptcy Probability variable which has no significant effect on the Timeliness of Submitting Financial Statements. However, simultaneously all variables have a significant effect on the Timeliness of Financial Statement Submission.